Virológia vizsgálatok étkezési és fűszerpaprikán előforduló uborka mozaik vírussal - Tóbiás, István; Almási, Asztéria; Csilléry, Gábor; Timár, Zoltán; Nemes, Katalin; Salánki, Katalin (GEORGIKON FOR AGRICULTURE, 2017)
In 2016 severe virus infection was observed in several pepper growing district. From virus infected samples originated from greenhouse and field Cucumber mosaic virus was detected. According to our earlier studies (late 70 and early 80 years) isolates belonged to CMV II. group, but this year CMV isolates equaly belonged to CMV I and II. groups. CMV tolerance was studied in two pepper varieties, but no substantial differences were observed in symptom appearence and severity and virus concentration, although in one of the variety infected in later developmental stage the virus movement was delayed. Interesting observation was that spicy pepper varieties containing tobamovirus resistance gene were more susceptible to CMV infection than pepper varieties without tobamovirus resistance gene.